Théorie du bien-être et politique économique - Pelletier, Gérard-R. (L'Actualité économique)

(untitled) (HEC Montréal, 1978)
After facing disappearance during the thirties, under the well known attack by Lionel Robbins and other economists, theoretical welfare economics seems to be more and more in use in spite of still shaky foundations. The concept of surplus, the measurement of preferences and the economic welfare function are apparently among the most promising approaches. Welfarists like Tinbergen and Bergson are not so far now from known anti-welfarists like Robbins and Myrdal. However, the issue of the debate between Pigou and Robbins has to be reconsidered before we can use welfare theory. New methodological arguments are presented that try to separate the shaft from the weed in the thesis of Pigou and Robbins. Some errors are found that have remained alive up to now. After a new light is shed on the controversy, it is fairly easy reconcile Pigou, Robbins, Bergson, Myrdal and Tinbergen. It is fortunate that we can reach such a consensus because the theory of economic policy badly needs renewed foundations to be able to cope with changing values, new patterns of distribution and other long range problems. A fresh start with the questions raised by welfare economics should ease the way towards these goals.